Key and evolving needs of service providers in women’s harm reduction centers during the COVID-19 pandemic - Azam Rahmani; Maryam Janatolmakan; Elham Rezaei; Malihe Tabarrai (Harm Reduction Journal)
Abstract Background Service providers at women’s harm reduction centers maintained direct contact with their clients throughout the COVID-19 pandemic, providing valuable insights into their evolving needs. This study aimed to explore these emerging needs from the perspective of service providers. Methods This qualitative study utilized conventional content analysis. Data were gathered through semi-structured face-to-face interviews conducted with ten service providers employed in women’s harm reduction centers situated across three Iranian provinces (Tehran, Khuzestan, and Kermanshah) between January and May 2023. Participant selection was guided by purposive sampling, specifically utilizing Maximum Variation Sampling. Results The findings of this study showed that service providers specifically need to alleviate credit constraints and control inflation. Additionally, the necessity for continuous monitoring, revision of evaluative criteria, centralization of shelters and drop-in centers, and adequate staffing was emphasized. The need for flexible regulations, clear job descriptions, improved accommodations, and sufficient equipment was also highlighted. Employee safety and effective judicial protection were among other important needs. This study also emphasized the need to change negative social attitudes and enhance professional development for social workers. Developing creative educational approaches and conducting rigorous needs assessments were also among the significant findings. These findings can help policymakers design more effective support programs for service providers and improve service quality by providing appropriate communication tools. Conclusion The findings of this study underscore the critical importance of policymakers addressing this spectrum of identified needs to ensure the effective delivery of harm reduction services for women, not only during the COVID-19 pandemic but also in similar future crises.